Effects of Corporate Social Responsibility as a Marketing Strategy on Consumer Behaviour - Alesgerov, Ismayil Murtuz Oglu (Digital Repository of Theses, 2026)
This study examines the influence of Corporate Social Responsibility (CSR) conceptualised as a multidimensional strategic marketing capability on behaviour of consumers within the United Kingdom. It specifically examines the effects of perceived CSR on customer satisfaction, customer loyalty, and the customer's purchase intention and the mediation role of brand likeability. The research design is pragmatic philosophy, mixed methods sequential explanatory design, which includes a quantitative approach (i.e. survey, 300 participants in the UK) and a qualitative approach (i.e. 10 individuals are interviewed). Quantitative analysis through Structural Equation Modelling (SEM) results showed that ethical, environment and philanthropic CSR dimensions have a significant and positive impact on customer satisfaction, loyalty and purchase intention. Brand likeability emerged as a partial mediator, which points to the role of this variable as an emotional bridge between CSR perception and behavioural outcomes. Furthermore, authenticity and brand-causer fit were found to bolster these effects and confirm the importance of credible and congruent CSR communication. The qualitative results complemented these results by revealing the way consumers interpret CSR authenticity and connect it to brand identity and personal values. The study concludes that CSR is most effective if embedded in corporate identity and communicated in a transparent manner. Theoretical implications strengthen CSR's place in stakeholder and relationship marketing theories, whereas managerial implications highlight authentic and well-aligned CSR practices that can generate consumer trust as well as competitive differentiation. Overall, the research adds to the existing literature on CSR as a value-creating mechanism for increasing consumer engagement and long-term brand equity.